Atmospheric microplastic emissions from land and ocean - Ioanna Evangelou; Silvia Bucci; Andreas Stohl (Nature, 2026)
Abstract Microplastics (MPs) are global pollutants 1 , yet their atmospheric distribution is poorly understood 2 . Although atmospheric MP measurements have become more abundant, estimates of emissions into the atmosphere vary by orders of magnitude 3,4 . Here we compile a global atmospheric MPs dataset and compare it with size-aligned MP model simulations. Our model simulations show two to four orders of magnitude overestimation of the measured global median atmospheric MP concentrations. Measured median concentrations over the ocean are 27 times lower than over the land (0.003 and 0.08 particles m −3 , respectively). Applying a simple scaling method, we estimate that oceanic emissions are lower in number than land-based emissions. The total global land-based and oceanic emissions are 6.1 × 10 17 (1.3 × 10 17 to 1.1 × 10 18 ) particles year −1 and 2.6 × 10 16 (2.7 × 10 15 to 5.0 × 10 16 ) particles year −1 , respectively. Our results indicate that fewer MP particles are emitted into the atmosphere than previously thought. Land sources dominate the number but not the mass emissions, indicating that MPs emission size distributions should be investigated further.